Scrolling through adolescence: unveiling the relationship of the use of social networks and its addictive behavior with psychosocial health - Caroline Brand; Camila Felin Fochesatto; Anelise Reis Gaya; Felipe Barreto Schuch; José Francisco López-Gil (Child and Adolescent Psychiatry and Mental Health, 2024)
Abstract Background Understanding the relationship of social network use and addictive behaviors with adolescent psychosocial health is crucial in today’s digital age. Aim To verify the associations between social network use, messaging applications, and the addictive behaviors to social network with psychosocial health in Spanish adolescents. Methods A cross-sectional study was developed with 632 adolescents, aged 12 to 17 years from the Region of Murcia, Spain. The assessment of social network use (Facebook, Twitter, Instagram, Snapchat, and TikTok) involved evaluating the frequency of use of each social network individually using a single-item scale with five response options. WhatsApp use (i.e., a messaging application) was evaluated in the same manner. The Short Social Networks Addiction Scale-6 Symptoms was employed to assess potential addictive behaviors to social network use. The psychosocial health was assessed using the Strengths and Difficulties Questionnaire. Generalized linear regression models were conducted, and predictive probabilities of having psychosocial health problems were calculated. Results The predicted probability of presenting psychosocial health problems in the medium users and high users of social networks was 19.3% (95% confidence interval [CI] 13.0 to 27.7), and 16.2% (95% CI 10.2 to 24.6) higher compared to low users, respectively. High usage of Instagram, TikTok, Snapchat, and Facebook was associated with increased probabilities of psychosocial health problems, with Facebook showing the highest probabilities, at 31.3% (95% CI 14.8 to 54.2) for medium users and 51.9% (95% CI 26.5 to 76.3) for high users. Additionally, adolescents with addictive behaviors to social network use had from 19.0 to 25.2% probabilities of experiencing psychosocial health problems. Finally, the highest probabilities of having psychosocial health problems were identified in adolescents with high addictive behaviors when using social networks (28.9%; 95% CI 19.3 to 40.8%) and the lowest in those with low addictive behaviors (6.8%; 95% CI 3.3 to 13.6%). Conclusion Adolescents who use social networks more frequently and exhibit more addictive behaviors related to their use are more likely to experience psychosocial health problems compared to those who do not. Facebook showed the strongest association, followed by Snapchat, Instagram, and TikTok. Our data also revealed that adolescents exhibit various signs of addictive behaviors to social network use.